Mi Basah Berbasis Tapioka, Tepung Kecambah Koro, dan Lele sebagai Makanan Alternatif Pencegah Stunting Bayi di Bawah 2 Tahun: Mi Basah Berbasis Tapioka, Tepung Kecambah Koro, dan Lele sebagai Makanan Alternatif Pencegah Stunting Bayi di Bawah 2 Tahun - Friska Citra Agustia; Amellia Kartika Cahyani; Gumintang Ratna Ramadhan; Kifayati Rosiyanti Dewi (Amerta Nutrition, 2026)
Background: Wet noodles made of tapioca, Jack Bean Sprout Flour (JBSF), and catfish can be applied as alternative protein sources to prevent stunting. Objectives: This study aims to determine the best formula of wet noodles made of tapioca, JBSF, and catfish based on the optimum protein, fat, and sensory quality. Methods: A Non-Factorial Randomized Block Design (RBD) was used. The treatment factor (P) is the proportion of tapioca:JBSF:catfish, consist of 6 proportions: P1 (50:40:10); P2 (50:30:20); P3 (50:20:30); P4 (50:10:30); P5 (50:0:50); and P6 (50:50:0) with 4 repetitions. Total protein and fat content were analyzed with ANOVA, while sensory quality with Friedman test. Both tests were continued with DMRT (significantly different if p-value<0.05). Results: P1 (50:40:10) is the best formula based on the effectiveness index (weight value multiplied by effectiveness value). P1 has 24.45%db of protein, 0.57%db of fat, 68.46%wb of water, 3.14%db of ash, and 71.81%db of carbohydrate. This formula has a texture of 1.98 (less chewy), a colour of 3.3 (quite yellowish white), an aroma of 2.4 (beany and fishy), and a taste of 3.46 (simply tastes of sprouts and catfish). Wet noodles have met the minimum 20% requirement for a "protein source" on nutritional labels under BPOM No. 1 of 2022. Conclusions: Per 40 g serving of P1 formula, wet noodles provide 156.13 kcal of energy, fulfilling 11.56% of the Recommended Dietary Allowance (RDA) for infants aged 1-3 years; it contains 9.79 g of protein (48.96%), 0.23 g of fat (0.51%), and 28.74 g of carbohydrate (13.29%).